ANALISA PERLINDUNGAN KONSUMEN SEBAGAI PENGGUNA INFORMATION TECHNOLOGY AND COMMUNICCATION - Noviyanti Wulandari Sitepu (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
Technological sophistication at this time was very easy and helped people who live in this age. Everything can be easily obtained in order to fullfill the needs of his life that everything can be obtained only through the sophistication of information technology and communication. Without having to meet with the seller or vice versa everything is so facilitated only through the sophistication of information technology and communication. But in other hands these advantages it turn out into those disadvantages also that result in losses to the buyer or consumer of course. Because without having not meeting face to face is difficult for consumers as buyers and users of the sophistication of information technology and communication to report or complain about the losses they suffer. So that there is a need for legal protection for consumers as buyers who are often harmed by the seller. And what about the responsibillity of the seller who has broken the law. It is expected that by this research consumers' rights will be fulfilled and the seller can be held accountable for his actions both in civil, criminal and state administration if they have violated the existing legal provisions. Thus no party is harmed or misused the sophistication of information technology and communication. Keywords: consumers, consumer protection, sellers / business actors, information technology communication.